Anterior Clinoid Metastasis Removed Extradurally: First Case Report - Pojskić, Mirza; Zbytek, Blazej; Arnautović, Kenan I. (Journal of Neurological Surgery Reports, 2018)
Background We report a case of isolated metastasis on the anterior clinoid process (ACP) mimicking meningioma.Clinical Presentation A 58-year-old male presented with headaches, right-sided visual disturbances, and blurred and double vision. The cause of double vision was partial weakness of the right III nerve, resulting from compression of the nerve by “hypertrophied” tumor-involved right anterior clinoid. Medical history revealed two primary malignant tumors—male breast cancer and prostate cancer (diagnosed 6 and 18 months prior, respectively). The patient was treated with chemotherapy and showed no signs of active disease, recurrence, or metastasis. Postcontrast head magnetic resonance imaging (MRI) showed extra-axial well-bordered enhancing mass measuring 1.6 × 1.1 × 1 × 1 cm (anteroposterior, transverse, and craniocaudal dimensions) on the ACP, resembling a clinoidal meningioma. Extradural clinoidectomy with tumor resection was performed via right orbitozygomatic pretemporal skull base approach. Visual symptoms improved. Follow-up MRI showed no signs of tumor residual or recurrence.Conclusion This is the first case report of a metastasis of any kind on ACP. Metastasis should be included as a part of the differential diagnosis of lesions of the anterior clinoid. Extradural clinoidectomy is a safe and effective method in the treatment of these tumors.
Keywords: anterior clinoid process; extradural clinoidectomy; metastasis; anterior clinoid metastasis; case report